Prevalence of Canine Hip Dysplasia in Switzerland Between 1995 and 2016—A Retrospective Study in 5 Common Large Breeds - Ohlerth, Stefanie; Geiser, Britta; Flückiger, Mark; Geissbühler, Urs (Frontiers in Veterinary Science, 2019)
Canine hip dysplasia (CHD) is a genetic disease, modulated by epigenetic and environmental factors. To decrease the prevalence of CHD, the hip joints of many pure breed dogs are radiographed to identify dysplastic dogs not qualified for breeding. It has been shown that both, prevalence and severity of CHD may be reduced on the basis of phenotypic i.e. radiographic selection of breeding animals. The method has been used in many countries for over 50 years. In the present study, severity and prevalence of CHD in five common large breeds in Switzerland were evaluated since 1995. Both, prevalence and severity of CHD dropped in each breed between the periods 1995-1999 and 2010-2016. The prevalence decreased in Golden Retrievers from 25% to 9% and in Labrador Retrievers from 16% to 3%, respectively. In the Flat-Coated Retriever, prevalence in general was low, decreasing from 6% to 3%. In the Bernese mountain dog and the German shepherd dog, a decrease from 21% to 12% and from 46% to 18%, respectively, was observed. However, the rather low overall rate of radiographed dogs (Retrievers: 11% to 18%, Bernese Mountain dogs: 23% and German Shepherd dogs: 31%) does not allow to draw reliable conclusions regarding the true prevalence of CHD for the entire population of these breeds in Switzerland.